Avaliação qualitativa das águas subterrâneas captadas em chafarizes públicos no município de Fortaleza, Ceará – Brasil - Silva, Mariane Pinto da (2016)
The Ceará faces its worst prolonged drought, since 1910, however, alternative sources of water resources are of vital importance in the face of such a critical scenario. Groundwater, under conditions of scarcity of rain, serves as a strategic water reserve. Groundwater abstraction through the construction of wells is common in the city of Fortaleza due to the need to meet the water demand required for private or public water supply, caused by periods of drought or shortage, as well as by the need to minimize expenses with treated water. This research has as main objective to evaluate the quality of the groundwater captured by public fountains of the municipality of Fortaleza. Samples of groundwater collected by 8 public fountains were collected. In the field stage, 3 samples, of alternating days, were collected in each fountain, totaling 24 samples collected. Physicochemical and bacteriological parameters were analyzed, according to Administrative Order No. 2914/2011, which is responsible in Brazil for determining the potability standards of water intended for human consumption. The results show that the water collected in public fountains is unfit for human consumption, both by physicochemical parameters and by bacteriological parameters. In terms of the presence of residual chlorine, all samples were unfit for human consumption, indicating that the waters were crude, ie natural, with no previous disinfection treatment. From the total of 24 samples, 19 presented values outside the standards required for nitrate (N-NO3 - ), indicating that these waters have contact with remote fecal contamination. Considering the bacteriological parameters, all 24 samples were considered unfit for human consumption, including pathogenic bacteria, which causes great concern due to waterborne diseases. The results obtained in the development of this research generate indications that the areas around the studied fountains show absence or deficiency of basic sanitation, mainly involving the process of domestic sewage disposal, since most of the samples presented high concentrations of nitrate (N-NO3 - ). Nitrate is considered the most frequent pollutant from septic systems. In view of the qualitative conditions of the groundwater collected in the fountains, the most efficient forms of disinfection treatment, in addition to chlorination in low nitrate concentrations, are ozonation, ultraviolet radiation (in Low turbidity), ultrafiltration and rapid filtration with filters optimized for this. Sequential coagulation / clarification treatments may be performed prior to in order to obtain better disinfection results. From the results obtained, it is necessary to constantly monitor the quality of water intended for human consumption, in addition to the need to treat disinfection of water, before consumption. The fountains, in which high concentrations of contaminants / pollutants have been obtained, must undergo further laboratory analysis as soon as possible. If high concentrations are recurring, and the causes are not identified or resolved, fountains should be banned. If problems persist without solutions, for more than 6 months, fountains must be completely inactivated, requiring well burial to deactivate the entire source.